Pemberdayaan Perempuan melalui Pelatihan Kewirausahaan, Inklusi Keuangan Digital, dan Penguatan UMKM Berbasis Gender Responsif sebagai Strategi Meningkatkan Kemandirian Ekonomi dan Daya Saing Usaha - Purwati Ratna Wahyuni; Sindi Arista Rahman; Ribut Santosa (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to empower women in Sumenep through entrepreneurship training, digital financial inclusion, and strengthening gender-responsive MSMEs in a sustainable community development context. The main problem identified was the low level of economic independence and competitiveness of women's businesses, particularly in the MSME sector. Therefore, this activity was designed with an approach that included entrepreneurship training to improve business skills, the implementation of digital financial inclusion to expand access to financial services, and strengthening MSMEs with a gender-responsive approach to increase competitiveness. The methods used in this activity included direct training, mentoring, and providing participants with access to relevant technology and information. The results of this activity indicate an increase in the economic independence and competitiveness of women's businesses in Sumenep, with the identification of a number of MSMEs that are growing and able to optimally utilize technology and digital financial services to support business sustainability and local economic development.